Measurement of the fracture energy in mode I of atmospheric ice accreted on different materials using a blister test - Pervier, Marie Laure A.; Hammond, David (Elsevier, 2019)
Atmospheric ice is formed when supercooled water droplets strike an object such as a tree, aircraft or wind turbine. Its microstructure and properties vary widely according to the flow and thermal conditions prevailing. The present work was conducted in the Cranfield Icing Wind Tunnel for a european project called STORM (efficient ice protection Systems and simulation Techniques Of ice Release on propulsive systeMs). It aimed at collecting data on the fracture energy of atmospheric ice on four different materials - AL2024-T3, Ti-6Al-4V, Platinum and Alexit-411 - using a blister test. This particular test, firstly introduced by Andrews and Lockington (1983), have been adapted by Cranfield University to be able to test the ice adhesion in situ while ice is still accreting on the surface making it closer to real situation. The second part of the paper will focus on the influence of different parameters like the materials ice is accreted on, the total ambient temperature, the tunnel wind speed and the cloud liquid water content which have been investigated over a few icing conditions
Keywords: Atmospheric ice; Fracture energy; Ice adhesion; Blister test